Bearers of meaning : the classical orders in antiquity, the Middle Ages, and the Renaissance - Onians, John, 1942- (Princeton University Press, 1988)
For all those interested in the relationship between ideas and the built environment, John Onians provides a lively illustrated account of the range of meanings that Western culture has assigned to the Classical orders. Onians shows that during the 2,000 years from their first appearance in ancient Greece through their codification in Renaissance Italy, the orders--the columns and capitals known as Doric, Ionic, Corinthian, Tuscan, and Composite--were made to serve expressive purposes, engaging the viewer in a continuing visual dialogue.--Publisher